CD44 v5 domain inhibition represses the polarization of Th2 cells by interfering with the IL‐4/IL‐4R signaling pathway. Issue 1 (16th December 2021) - Yang, Chun; Lin, Jianhong; Liang, Hongyan; Xue, Li; Kwart, Ariel; Jiang, Meng; Zhao, Jianjun; Ren, Huan; Jiang, Xiaofeng; Munshi, Nikhil C
Abstract: The balance between T helper type 1 (Th1) and T helper type 2 (Th2) cells is critical for both innate and acquired immune reactions. However, the precise mechanisms of T helper‐cell differentiation remain unclear. As an important T‐cell activation molecule, CD44 participates in the differentiation of Th1 and Th2 cells. We demonstrated that CD44 variant exon v5 (CD44 v5) is highly expressed by induced human Th2 cells. To investigate the role of the CD44 v5 domain in Th2 cell differentiation, we treated human CD4 + T cells with anti‐CD44v5 antibody and observed that the levels of phosphorylated STAT6 and GATA3 and the secretion of interleukin‐4 (IL‐4) were significantly decreased after the treatment. We also further found that the inhibition of Th2 differentiation was caused by the degradation of the alpha chain of IL‐4 receptor (IL‐4Rα), the CD44 v5 domain colocalized with IL‐4Rα on cell surface and the degradation of IL‐4Rα increased after CD44 v5 domain blocking or ablating. Our results indicated that CD44v5 antibody treatment interrupted the interaction between CD44 v5 domain and IL‐4Rα, but the CD44 v5 domain blockage would not spoil the colocalization between IL‐4R expression and T‐cell receptor and the immunological synapse formation; similar results were also found in CD44v5‐deficient CD4 + T cells. In conclusion, we revealed the function of the CD44 v5 domain in Th2 cell differentiation; blocking or ablating the CD44 v5 domain could accelerate IL‐4Rα degradation and then induce the Th2 cell inhibition. Abstract : In this study, we found that the CD44 variant exon v5 (CD44 v5) domain was highly expressed on Th2 cells compared with control cells. In particular, blockade or loss of human CD44 v5 domain achieved through standard experimental approaches increased the degradation of the alpha chain of the interleukin‐4 (IL‐4) receptor (IL‐4Rα), which led to an attenuation of signaling events critical for Th2 polarization.